EUTECTIC CRYSTALLIZATION IN THE UNDERCOOLED ORTHOCLASE-QUARTZ-H2O SYSTEM: EXPERIMENTS AND SIMULATIONS - Baker D.R.; Freda C. (My University, 2001)
Textures formed during crystallization of the eutectic composition in the system Orthoclase-Quartz-H2O at 500 MPa and 50, 100, and 200 degreesC undercooling have been studied experimentally and simulated using a two-dimensional Ising model. The experiments performed at 50 degreesC undercooling did not produce complex, interesting textures but only very rare, isolated K-feldspar and quartz crystals. At 100 degreesC undercooling the most common texture is a fine-grained, submicrometre to micrometre-scale, spherulitic quartz-K-feldspar intergrowth; set within this intergrowth are larger individual crystals of quartz or K-feldspar. Experiments performed at 200 degreesC undercooling are remarkable for the occurrence of micrometre-scale graphic textures and millimetre scale spherulitic textures, characterized by quartz-K-feldspar intergrowths in the core and dominated by K-feldspar at the rims. Simulations of crystal growth, performed to complement and to interpret the experimental products, investigated what combination of growth (G) and diffusion (D) conditions can give rise to the crystal shapes and textures found in the experiments. These conditions correspond to growth rates between similar to 1 x 10(-10) and 5 x 10(-9) m s(-1) and diffusion coefficients between 10(-17) m(2) s(-1) in the melt phase and 10(-8) m(2) s(-1) in the fluid phase. The simulations, despite their limitations, provide textures similar to the experimental ones. In particular, simulations produced a quartz-K-feldspar intergrowth when G = D and singular large quartz and K-feldspar crystals when G < D. These changes in the G:D ratio, in the experiments and in natural rocks, are attributed to a change in the growth of the crystal from a silicate melt to an aqueous fluid. The most interesting results of this study are that highly undercooled melts of a simplified pegmatite composition produce textures remarkably similar to natural pegmatites and that simulations provide a powerful tool to understand what processes cause these textures in experimental run products and natural rocks.